Analysis of the Weakening Economy on Financial Resilience in the Tourism Industry in Surabaya During the Covid-19 Pandemic - Meilita Rizkynanda; Argaleka Ayu Candraningsih; Titus Gustiagung Grace Widya Arta; Maria Yovita R Pandin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine financial resilience , potential and ways to maintain the economy during the COVID-19 pandemic for the tourism industry in Surabaya. this study uses qualitative methods with several tourist objects in the city ofSurabaya . From the results of the study, the economic decline experienced by the tourism industry in Surabaya was caused by a decrease in the number of visitors , resulting in difficulties in managing tourist spots , existing facilities and decreased income .